Yes Sister, No Sister : My Life as a Trainee Nurse in 1950s Yorkshire - Craig, Jennifer (Ebury Publishing, 2010)
A trainee nurse in the 1950s had a lot to bear. This title introduces these warm-hearted yet naive young girls as they get to grips with strict discipline, long hours and bodily fluids. It shows the camaraderie that develops in evening study sessions, sneaked trips to the cinema and mischievous escapades with the young trainee doctors.
Keywords: Nurses -- England--Leeds -- Leeds General Infirmary